INFLUENCE OF MICROBIOLOGICAL FERTILIZERS ON SOIL FERTILITY AND CROPS YIELD (Scientific journal of the Fergana State University, 2025)
The article presents the results of studies of microbiological fertilizers prepared from a mixture of various microorganisms on cotton and grain crops to increase soil fertility and crop productivity. According to the results of the experiments, it was noted that the cotton yield increased by 8.5 c/hе, and the grain yield by 10.7 c/hе in comparison with the control. The number of reproduction of microorganisms in the soil also increased by 9-16 million propagules.